Somebody's daughter [compact disc, unabridged] : a memoir - Ford, Ashley C. (Macmillan Audio, 2021)
One of the most prominent voices of her generation debuts with an extraordinarily powerful memoir: the story of a childhood defined by the ever-looming absence of her incarcerated father and the path we must take to both honor and overcome our origins.